Comparison of the Percentage Stance and Swing Phases and Ground Reaction Force between Young and Older Adults during Walking at different speeds - Neda Brooshak; Mousa Asadi; Seyyed Hossein Hosseini (Islamic Azad University, Hamedan Branch, 2017)
Objective: comparing the effects of gait at different speeds on spatiotemporal and kinetic parameters can result in better perception of gait pattern differences between young and older adults. Thus the purpose of this study was to compare the percentage of gait stance and swing phases and vertical ground reaction force between young and older adults during walking with different speeds. Methods: 20 young and 20 older adult men with mean age of 25.73 and 66.54 years old respectively, were selected via nonrandom sampling. the percentage of stance and swing phases gait cycle and vertical ground reaction force (VGRF) in stance subphases including weight acceptance, midstance and push off during walking at a 10-meter pathway with slow, medium, and fast speeds, were measured by Kistler Force plate. The data were analyzed running ANOVA with repeated measures and Bonferronii tests. Results: The results showed that in both age groups, with increasing walking speed, the percent of stance phase would decrease and the percent of swing phase was increased (P<0.01), there was not a significant difference between two groups (P>0.05). Also, at slow speed, there was no significant difference in vertical ground reaction force between two age groups (p>0.05). But, there were significant differences in the VGRFs of weight acceptance and push off phases at medium and fast speeds, between two groups (p<0.01). In addition, there were significant differences at VGRFs of weight acceptance and push off phases between different speeds (p<0.01). Conclusion: In general, the percentage of stance and swing phases of a gait cycle is similar between young and older adults. Lower VGRFs of weight acceptance and push off phases in the elders reflects the weakness of the knee extensor, hip extensors and ankle plantar flexors. It seems that older adults reduce the rate of force production during fast gait to achieve the necessary capacity for power generation and thereby, overcome the weakness of the lower extremity muscles.